Melacak Arti dan Makna Tarum, Tarumanagara, Ci Tarum, dan Pataruman melalui Pendekatan Linguistik, Sejarah, dan Budaya - Isnendes, Chye Retty; Supendi, Usman; Hidayat, Asep Achmad; Nuwangi, Pohaci Puspa; Kusumawardhana, Gelar Taufiq (Jurnal Pendidikan Bahasa dan Sastra, 2023)
The plant is called tarum in Sundanese, nila in Sanskrit and indigo in English. This plant is considered a source of inspiration for place naming (toponymy) in Sundanese landscape. Some of the places and natural phenomena that are considered to be inspired by the tarum plant are Ci Tarum as the largest river in Sundanese landscape, Tarumanagara as the kingdom with the oldest epigraphic evidence in landscape Sundanese, and Pataruman which is historically believed to be the center of tarum processing activities that produce natural blue dye. There are still other variations of names with the word tarum, such as Tarumajaya located in the southern area of Bandung in the upstream area of Ci Tarum and Banjar Patroman (Banjar Pataruman) located in the eastern area of Priangan, which is believed by the surrounding community to be one of the centers of tarum processing in the past. The naming of places and natural phenomena is an important linguistic phenomenon in the cultural aspects of Sundanese society that requires critical, fundamental and analytical analysis. Thus, conceptual precision that relies on the meaning and basic meaning of tarum as a working tool for disclosing information and knowledge that is more holistic and comprehensive, is expected to open up insights and provide valuable contributions regarding the cultural construction and historical aspects of Sundanese society in the past in landscape Sundanese more clearly and accurately.